Diagnóstico hidroambiental para incremento da qualidade ambiental no município de Votorantim, SP - Naccarati, Ricardo de Paula Santos [UNESP] (2015)
The decline of ecosystems promotes the populational isolation of fauna and flora species, preventing them to continuing their fair existential perpetuations, towards their inherent evolutions that each species has the right to follow. Therefore, becomes needed large habitat parcels in order to maintain and ensure the permanence of the extraordinary biodiversity of São Paulo State. In order to contribute to the environmental development in the city of Votorantim, SP, this study conducted hydro-environmental diagnosis in strategic areas of the municipality potential to creation of Natural Public Parks. For this, the two main areas selected were physically and spatially delimited using geoprocessing techniques, when were cataloged the springs and streams, and made collections of water and sediment samples for laboratory tests to determine their physical, chemical, bacteriological and heavy metals characteristics to their respective frameworks before the values set by the relevant legislation. The hydro-environmental diagnosis of the selected areas allowed the observation of the existence of positive and negative impacts on the environment. From there have been proposed planned actions to environmental conservation and recovery aiming due creations of Natural Public Parks. Besides the hydro-environmental diagnosis for legally creation protected areas in Votorantim, the purpose of this study supplements by means of the aid to the native species perpetuation in the region, by favoring the establishment of large wildlife corridors between healthy forest remnants and thereby to contribute to the guarantee the provision of environmental services essential to the life quality of all